PENGARUH UKURAN ASET PERUSAHAAN DAN DIVIDEND PAYOUT RATIO (DPR) TERHADAP NILAI PRICE BOOK VALUE (PBV) PERUSAHAAN PLASTIK & KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hippy, Mohammad Zubair; Makur, Dharmawaty S. (JSAP : Journal Syariah and Accounting Public, 2022)
Abstract:The research is quantitative research using secondary data obtained from the site of the indonesia stock exchange.The size of the population in this research as many as 15 companies, then with the purposive sampling so obtained the number of samples from 10 companies.Data analysis techniques of the research is multiple regression analysis of the pooled data. The results of this study indicate that (1) the size of company assets has a positive and significant effect on the Price book value of plastic and packaging companies. (2) Dividend Payout Ratio has no significant positive effect on the Price book value of plastic and packaging companies. (3) The size of the company's assets and the Dividend Payout Ratio together have a significant effect on the Price book value of plastic and packaging companies with a determinant value of 78.0867%. The ability of other variables to explain the value of the company is 21.9133%, namely the variable liquidity ratios, audit committees, independent commissioners, profitability ratios, solvency ratios, management decisions, company ownership structure and earnings per share of the company. Keywords: Price book value, Size of company assets, Dividend Payout Ratio Abstrak:Penelitian ini merupakan penelitian kuantitatif dengan menggunakan data sekunder yang diperoleh dari situs Bursa Efek Indonesia. Jumlah populasi dalam penelitian ini sebanyak 15 perusahaan, kemudian dengan metode purposive sampling sehingga diperoleh jumlah sampel sebanyak 10 perusahaan. Teknik analisis data dalam penelitian ini adalah analisis regresi berganda data panel. Hasil penelitian ini menunjukan bahwa (1) Ukuran aset perusahaan berpengaruh positif dan signifikan terhadap nilai Price book value perusahaan plastik & kemasan. (2) Dividend Payout Ratio berpengaruh positif tidak signifikan terhadap nilai Price book value perusahaan plastik & kemasan. (3) Ukuran aset perusahaan dan Dividend Payout Ratio secara bersama-sama berpengaruh signifikan terhadap nilai Price book value perusahaan plastik & kemasan dengan nilai determinan sebesar 78,0867%. Adapun kemampuan dari variabel lain dalam menjelaskan nilai perusahaan sebesar 21.9133% yakni variabel rasio likuiditas, komite audit, komisaris independen, rasio profitabilitas, rasio solvabilitas, keputusan manajemen, struktur kepemilikan perusahaan serta laba per lembar saham perusahaan. Kata Kunci : Price book value, Ukuran aset perusahaan, Dividend Payout Ratio